Do adult focused anti-smoking campaigns have an impact on adolescents? The case of the Australian National Tobacco Campaign. (23rd July 2003) - White, V; Tan, N; Wakefield, M; Hill, D
Abstract : Objectives: To examine adolescents' awareness of and response to an adult focused anti-smoking advertising campaign. Design and setting: Data were obtained from two cross sectional surveys of adolescents. The first study, a national evaluation study, involved a telephone survey of a randomly selected sample of 400 14–17 year olds across Australia in 1998. The second study involved a survey of 3714 students aged 12–17 years, randomly selected from a probability sample of secondary schools in the Australian State of Victoria. Main outcome measures: In both surveys, adolescents answered questions on their awareness of the advertising campaign and actions taken in response to the campaign. Adolescents in the national evaluation study also answered questions assessing knowledge of health effects of smoking, impact of the campaign on adolescents, and relevance of the campaign for adolescents and other groups. Responses for smokers and nonsmokers were examined. Results: Among the national evaluation sample, 85% of adolescent smokers thought the campaign was relevant to them. Fifty three per cent indicated that the campaign had led some teenagers to at least try to quit and 85% thought it made smoking seem less cool and desirable. Among students who were established smokers the campaign generated quitting activity, with 27% cutting down the number of cigarettes they smoked and 26% having thought about quitting. Conclusion: Results indicate that adolescents were very aware of this adult focused anti-smoking campaign and thought it relevant to them. The findings suggest that a graphic health effects cessation focused campaign may have been successful in promoting anti-smoking attitudes among adolescents.